Keanekaragaman Jamur Basidiomycota di Danau Perintis Provinsi Gorontalo - Herinda Mardin; Ani M Hasan; Wirnangsi Din Uno (Mahesa Research Center, 2023)
Lake Perintis is a strategic lake as a tourist spot that has unspoiled environmental conditions that have the potential to find various types of macroscopic fungi, especially Basidiomycota fungi. Macroscopic fungi are a group of cellulose degrading fungi which have a very important role for the environment. This study used a quantitative descriptive method with field sampling using an exploratory survey method. This method aims to make direct observations in all research locations in order to obtain more in-depth data. This study aims to determine the diversity of types of Basidiomycota fungi found in Lake Perintis. By using the field note form to identify the fungi in the Perintis lake location. The results showed that Lake Perintis has a type of Basidiomycota fungi consisting of 2 class, 5 ordo, 10 family, 18 genus and 21 species.